Pathways from the early language and communication environment to literacy outcomes at the end of primary school; the roles of language development and social development. (4th March 2021) - Gibson, Jenny L.; Newbury, Dianne F.; Durkin, Kevin; Pickles, Andrew; Conti-Ramsden, Gina; Toseeb, Umar
ABSTRACT: The quality of a child's early language and communication environment (ELCE) is an important predictor of later educational outcomes. However, less is known about the routes via which these early experiences influence the skills that support academic achievement. Using data from the Avon Longitudinal Study of Parents and Children (n = 7, 120) we investigated relations between ELCE (<2 years), literacy and social adjustment at school entry (5 years), structural language development and social development in mid-primary school (7–9 years), and literacy outcomes (reading and writing) at the end of primary school (11 years) using structural equation modelling. ELCE was a significant, direct predictor of social adjustment and literacy skills at school entry and of linguistic and social competence at 7–9 years. ELCE did not directly explain variance in literacy outcomes at the end of primary school, instead the influence was exerted via indirect paths through literacy and social adjustment aged 5, and, language development and social development at 7–9 years. Linguistic and social skills were both predictors of literacy skills at the end of primary school. Findings are discussed with reference to their potential implications for the timing and targets of interventions designed to improve literacy outcomes.